Translation Initiation Factor eIF4E and eIFiso4E Are Both Required for Peanut stripe virus Infection in Peanut (Arachis hypogaea L.) - Xu, Manlin; Xie, Hongfeng; Wu, Juxiang; Xie, Lianhui; Yang, Jinguang; Chi, Yucheng (Frontiers in Microbiology, 2017)
Peanut stripe virus (PStV) belongs to the genus Potyvirus and is the most important viral pathogen of cultivated peanut (Arachis hypogaea L.). The eukaryotic translation initiation factor, eIF4E, and its isoform, eIF(iso)4E, play key roles during virus infection in plants, particularly Potyvirus. In the present study, we cloned the eIF4E and eIF(iso)4E homologs in peanut and named these as PeaeIF4E and PeaeIF(iso)4E, respectively. Quantitative real-time PCR (qRT-PCR) analysis showed that these two genes were expressed during all growth periods and in all peanut organs, but were especially abundant in young leaves and roots. These also had similar expression levels. Yeast two-hybrid analysis showed that PStV multifunctional helper component proteinase (HC-Pro) and viral protein genome-linked (VPg) both interacted with PeaeIF4E and PeaeIF(iso)4E. Bimolecular fluorescence complementation assay showed that there was an interaction between HC-Pro and PeaeIF4E/PeaeIF(iso)4E in the cytoplasm and between VPg and PeaeIF4E/PeaeIF(iso)4E in the nucleus. Silencing either PeaeIF4E or PeaeIF(iso)4E using a virus-induced gene silencing system did not significantly affect PStV accumulation. However, silencing both PeaeIF4E and PeaeIF(iso)4E genes significantly weakened PStV accumulation. The findings of the present study suggest that PeaeIF4E and PeaeIF(iso)4E play important roles in the PStV infection cycle and may potentially contribute to PStV resistance.